Relationships between parenting style and sibling conflicts: A meta-analysis - Liu, Cong; Rahman, Mohd Nazri Abdul (Frontiers in Psychology, 2022)
Previous studies have shown that sibling conflicts are detrimental to physical and psychological development, as well as long-term human development. Although many studies have discovered relations between parenting style and sibling conflicts, these findings were contentious and did not provide a universal solution. Therefore, the meta-analysis was used as the method to determine the nature and magnitude of the relationships. There were a total of 9287 participants in the 16 included studies, from which 52 effect sizes were extracted. According to the overall meta-analysis results, authoritative parenting(r=-0.227) did have the potential to reduce sibling conflicts. Neglecting(r=0.373), inconsistent(r=0.364), indulgent(r=0.304), and authoritarian(r=0.231) parenting styles were related to sibling conflicts in a positive way. Moreover the study investigated the effectiveness of several moderator variables, such as children’s age, region of participants, publication language and publication year. The research indicates that authoritative parenting as a protective factor of sibling conflicts. In addition preschooler sibling conflicts were more likely to be exacerbated by neglecting and inconsistent parenting styles, and among school-age children by indulgent parenting. Asian parents, in particular, needed to be wary of inconsistent parenting, which had a strong effectiveness on sibling conflicts in Asia. And the effectiveness of authoritative parenting style on sibling conflicts grows over time.